Some results on the solution of the neoclassical growth model - Jesus Fernandez-Villaverde; Juan Francisco Rubio-Ramírez (Federal Reserve Bank of Atlanta, 2003)
This paper presents some new results on the solution of the stochastic neoclassical growth model with leisure. We use the method of Judd (2003) to explore how to change variables in the computed policy functions that characterize the behavior of the economy. We find a simple closed-form relation between the parameters of the linear and the loglinear solution of the model. We extend this approach to a general class of changes of variables and show how to find the optimal transformation. We thus reduce the average absolute Euler equation errors of the solution of the model by a factor of three. We also demonstrate how changes of variables correct for variations in the volatility of the economy even if we work with first-order policy functions and how we can keep a linear representation of the model's laws of motion if we use a nearly optimal transformation. We conclude by discussing how to apply our results to estimate dynamic equilibrium economies.
Keywords: 330